CALCULATION OF WATER QUALITY INDEX AND PHYSICO-CHEMICAL ANALYSIS OF PRAVARA RIVER WATER AHMEDNAGAR DISTRICT (MAHARASHTRA) - Gadekar, Deepak Janardhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Water is a natural resource, human life is impossible without water. Water is used by humans for various purposes, but various overuses by humans are causing water scarcity. The most important reason behind this is the increasing population and the increasing consumption of water, which is being released into rivers, streams, lakes, seas, oceans, causing a large amount of water pollution. The present investigations of the comparative study of Calculation of Water Quality Index and Physico-chemical Analysis of Pravara River water in Ahmednagar district of Maharashtra. The samples were collected in sterilized polythene bottles of one litter capacity monitoring were done during January 2023 and November 2023. There are 12 Physico- chemical parameters having test observed in four sampling sites along the course of Pravara River. The streams from catchments area Wilson dam, Nilwande , Kalas and Ashwi . Water samples were collected during morning hours. Physico-chemical parameters include , pH and chemical parameters are tested Conductivity, Calcium, Magnesium, Sodium, Palash, Carbonate, Bio -carbonate, Chloride, Sulfate, Sodium Stable Ratio, Residual Sodium Carbone. Calculations of water quality index and physico-chemical analysis of water have been done during pre-monsoon and post-monsoon periods.